Rewolucja przemysłowa i jej wpływ na rynek pracy IT - Beata Kuźmińska-Sołśnia (Edukacja Ustawiczna Dorosłych)
The article highlights the current technological changes as well as the digitization and automation process, which was significantly accelerated by the COVID-19 pandemic. It also presents the results of a survey conducted among employers in the IT sector in Radom region which confirmed the demand for employees of various IT specializations and well developed soft skills. High IT qualifications and interpersonal skills ensure a great start into the professional future.